History of Trade Relations in Uzbekistan (Mid-20s of the Twentieth Century) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article briefly describes the history of trade relations and the economic situation of Uzbekistan, as well as the unique way of organizing markets. On the eve of the zoning carried out in Uzbekistan and after 1926, markets operated in republican cities, regional centers and large villages. Trading activities carried out in the regions were analyzed based on various sources.